2023
DOI: 10.1093/jcag/gwac036.154
|View full text |Cite
|
Sign up to set email alerts
|

A154 Cancers Associated With Inflammatory Bowel Disease in Canada: A Population-Based Analysis of Cases and Matched Controls

Abstract: Background Individuals with inflammatory bowel disease (IBD) are known to have a higher risk of digestive tract cancers and cancers associated with immunosuppression. As the IBD population is ageing, age-related cancers may be more commonly diagnosed. Purpose To assess whether IBD patients were at a higher odds of incident cancers than their matched controls stratified by age above and below 65 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The results of the leave‐one‐out meta‐analysis for the primary study outcome have been summarised in Figure S2; no single study significantly influenced the risk estimate. The Galbraith plot identified one outlier study 23 (Figure S3), which might be due to being a conference abstract or the sole study reporting OR as an effect measure; after removing this study, the risk of pancreatic cancer was still increased in IBD (RR = 1.45 [95% CI: 1.18–1.79]), with moderate heterogeneity ( I 2 = 71.9%, p for χ 2 = 0.02). Finally, the annual incidence of pancreatic cancer caused by IBD increased by 55 cases (95% CI: 17–103) per million.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the leave‐one‐out meta‐analysis for the primary study outcome have been summarised in Figure S2; no single study significantly influenced the risk estimate. The Galbraith plot identified one outlier study 23 (Figure S3), which might be due to being a conference abstract or the sole study reporting OR as an effect measure; after removing this study, the risk of pancreatic cancer was still increased in IBD (RR = 1.45 [95% CI: 1.18–1.79]), with moderate heterogeneity ( I 2 = 71.9%, p for χ 2 = 0.02). Finally, the annual incidence of pancreatic cancer caused by IBD increased by 55 cases (95% CI: 17–103) per million.…”
Section: Resultsmentioning
confidence: 99%
“…For this systematic review and meta-analysis, we screened 5201 citations from the initial database search. After excluding 5188 publications because of duplication or unsuitability, we identified 13 eligible articles, including 11 cohort studies regarding the first study aim 5,[8][9][10][11][22][23][24][25][26][27] and two studies concerning the second study aim. 28,29 The search strategy and process for study selection are illustrated in Figure 1.…”
Section: Search Results Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most population-based studies have reported CRC risk to be elevated among persons with IBD as compared to age- and sex-similar persons without IBD ( 18 , 20 , 21 , 23 , 59 ). A meta-analysis of population-based studies up to 2009 reported a standardized incidence ratio (SIR) of 1.7 (95% confidence interval [CI]: 1.2, 2.2) for CRC among persons with IBD relative to the general population, which was similar across Crohn’s disease and ulcerative colitis ( 18 ).…”
Section: Epidemiology Of Cancer In Ibdmentioning
confidence: 99%